Correlation between reported dengue illness history and seropositivity in rural Thailand - Darunee Buddhari; Kathryn B. Anderson; Gregory D. Gromowski; Richard G. Jarman; Sopon Iamsirithaworn; Butsaya Thaisomboonsuk; Taweewun Hunsawong; Anon Srikiatkhachorn; Alan L. Rothman; Anthony R. Jones; Stefan Fernandez; Stephen J. Thomas; et al. (PLoS neglected tropical diseases, 2021)
In the latest World Health Organization (WHO) recommendation for Dengvaxia implementation, either serological testing or a person's history of prior dengue illness may be used as supporting evidence to identify dengue virus (DENV)-immune individuals eligible for vaccination, in areas with limited capacity for laboratory confirmation. This analysis aimed to estimate the concordance between self-reported dengue illness histories and seropositivity in a prospective cohort study for dengue virus infection in Kamphaeng Phet province, a dengue-endemic area in northern Thailand. The study enrolled 2,076 subjects from 516 multigenerational families, with a median age of 30.6 years (range 0-90 years). Individual and family member dengue illness histories were obtained by questionnaire. Seropositivity was defined based on hemagglutination inhibition (HAI) assays. Overall seropositivity for DENV was 86.5% among those aged 9-45 years, which increased with age. 18.5% of participants reported a history of dengue illness prior to enrollment; 30.1% reported a previous DENV infection in the family, and 40.1% reported DENV infection in either themselves or a family member. Relative to seropositivity by HAI in the vaccine candidate group, the sensitivity and specificity of individual prior dengue illness history were 18.5% and 81.6%, respectively; sensitivity and specificity of reported dengue illness in a family member were 29.8% and 68.0%, and of either the individual or a family member were 40.1% and 60.5%. Notably, 13.4% of individuals reporting prior dengue illness were seronegative. Given the high occurrence of asymptomatic and mild DENV infection, self-reported dengue illness history is poorly sensitive for prior exposure and may misclassify individuals as 'exposed' when they were not. This analysis highlights that a simple, highly sensitive, and highly specific test for determining serostatus prior to Dengvaxia vaccination is urgently needed.
Keywords: Mosquito-borne diseases and control; Viral Infections and Vectors; Malaria Research and Control